Analisis Fatwa DSN-MUI dan Fatwa di Negara Malaysia Terhadap Akad Mudharabah Dalam Perspektif Ulama - Hardiati, Neni; F, Fitriani; Nugroho, Wahyu (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This article attempts to analyze the fatwas in Indonesia (DSN-MUI) with the fatwas in Malaysia (MPS-BNM), the fatwas that are analyzed are more specific to the mudharbah agreement of the two fatwa institutions. from the fatwa in issuing a fatwa, in terms of definition, pillars and requirements, as well as the application of fatwa in Islamic banking in both countries. The data sources in this study were the MUI DSN fatwa and the MPS-BNM fatwa on the mudharbah agreement. Then analyzed with a comparison of the jurisprudence of the four schools of thought, books, and other articles using qualitative methods with a normative juridical approach. From the results of the analysis, it can be concluded that both the DSN-MUI and MPS-BNM fatwas use a lot of shafi'i schools of reference. Then, seen from the fatwa of the mudharbah agreement, the MUI DSN fatwa is more strict and moderate, while the MPS BNM is more flexible but moderate.